2013
DOI: 10.1007/s10964-013-0047-x
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Cyber Dating Abuse Among Teens

Abstract: Recent advancements in technology (e.g., social networking, texting) have created new ways for dating youth to relate to one another, including in abusive ways via "cyber dating abuse." Cyber dating abuse is a form of teen dating violence that overlaps with other types of abuse (e.g., psychological) but also has several unique characteristics. Given the phenomenon's limited presence in dating violence literature, we focus on identifying how experiencing cyber dating abuse relates to youths' individual behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
167
1
19

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(195 citation statements)
references
References 17 publications
8
167
1
19
Order By: Relevance
“…This could be part of a larger pattern of sexual coercion. Therefore, nonconsensual sexting could be indicative of forms of relational abuse (Perkins et al, 2013;Zweig et al, 2014). Future research could thus investigate how some forms of sexting possibly occur within the context of (cyber)dating abuse.…”
Section: Discussionmentioning
confidence: 99%
“…This could be part of a larger pattern of sexual coercion. Therefore, nonconsensual sexting could be indicative of forms of relational abuse (Perkins et al, 2013;Zweig et al, 2014). Future research could thus investigate how some forms of sexting possibly occur within the context of (cyber)dating abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Zweig, Dank, Yahner, and Lachman (2013) conducted a survey study of 5,647 middle and high school students assessing sexual and non-sexual cyber dating abuse, finding that 26% of students were victims of cyber dating abuse in the past year, and female students reported greater rates of victimization than male students. Another study using the same sample (focusing on the 3,745 youth with dating experience) found that experiencing cyber dating abuse was associated with delinquent behaviors and depressive symptoms, even more so than other types of dating violence (Zweig, Lachman, Yahner, & Dank, 2014). Among young adults, Bennett and colleagues (2011) surveyed 437 college students to compare electronic victimization among friends and dating partners.…”
Section: Digital Media Use and Dating Violencementioning
confidence: 99%
“…Otras conductas de riesgo que se pueden dar entre adolescentes son el ciberbullying (Alfaro et al, 2015;Belsey, 2005;Del Rey et al, 2011;Giménez, Maquilón & Arnaiz, 2015), el happy slapping (Valero, Sala & Moran, 2006), el sexting (Alfaro et al, 2015;Houck et al, 2014;), la sextorsión (Kopecký, 2014), el grooming (Alfaro et al, 2015;Davidson & Gottschalk, 2011;Katz, 2013) o el dating violence (Durán & Martínez-Pecino, 2015;Zweig, Lachman, Yahner & Dank, 2014). Las posibilidades de las TIC no son, por tanto, sólo lúdicas y académicas, sino que también hay que contemplar la existencia de un uso con finalidades violentas y delictivas (Alfaro et al, 2015;Agustina, 2010;Buelga, Cava & Musitu, 2010;Chóliz & Villanueva, 2011).…”
Section: Usos Y Abusos De Las Tic En Los Adolescentes Rie 2018 36(1unclassified